Free Flap Monitoring Using Infrared Thermography: An Objective Adjunct to Clinical Monitoring - Singla, Priyanka; Dixit, Pawan Kumar; Kala, Prakash Chandra; Katrolia, Deepti; Karmakar, Shilpi; Humnekar, Akhilesh; Singh, Apoorva Pratap (Indian Journal of Plastic Surgery, 2024)
Background Early detection of free flap compromise is critical for salvage of the flap. Various methods of free flap monitoring have been described, but clinical assessment is the standard method for among all. In this study, role of infrared thermography is evaluated for free flap monitoring.Materials and Methods In patients undergoing free flap surgery, monitoring was done using standard clinical parameters and infrared thermography as per our institutional protocol. Mean temperature difference (∆T) between the flap and the surrounding skin was calculated using the temperature readings from the thermal images intra- and postoperatively. The accuracy of infrared thermography in flap monitoring was assessed in comparison to the standard clinical protocol.Results Forty-one flaps were included in the analysis, out of which five flaps got compromised. It was observed that the mean temperature difference was higher (mean ∆T 0.20–0.59 vs. 2.38–3.32) when there was a flap compromise, and this temperature difference was evident even before the development of clinical signs. The temperature difference in venous thrombosis (mean ∆T 1.0–2.7) was found to be slightly lower than in arterial insufficiency (mean ∆T 2.1–4.4). For a ∆T cutoff value of 2°C, the thermal camera had a sensitivity of 88.6%, specificity of 98.9%, positive predictive value of 93.9%, and negative predictive value of 97.7%.Conclusion Infrared thermography is a valuable and noninvasive objective tool in free flap monitoring, which can detect flap compromise (increasing value of ∆T) even before it becomes clinically evident.
Keywords: thermal imaging; free flaps; infrared thermography; free flap monitoring